Simulation of a Mathematical Model of Proteins Interaction on GLUT4 Translocation - Ari Kusumastuti; Mohammad Isa Irawan; Kistosil Fahim; Nurul Anggraeni Hidayati; Anindita Sharkar ((IJCSAM) International Journal of Computing Science and Applied Mathematics, 2024)
Glucose is the energy source of cells. Glucose absorption into muscle cells is regulated by Insulin by involving the interaction of several proteins in a specific system. The system works for the translocation of GLUT4 to the cell membrane. GLUT4 is a transporter protein owned by every muscle cell, as an entry gate for glucose and an Insulin partner in maintaining homeostasis of blood glucose levels. After the Insulin activation occurs in the Insulin Receptor Substrate (IRS), it is followed by the activation of several proteins to regulate GLUT4 translocation, namely IRS, phosphatidylinositol 3-kinase (P13K), 3-phosphoinositide-dependent protein kinase-1 (PDK1/2) and serine/threonine-protein kinase (AKT). This study describes these processes in a mathematical model as a system of ordinary differential equations. The specific process modeled is the Insulin signal pathway that regulates GLUT4 translocation, which can be accessed on Kegg.jp. Moreover, string.db.org analysis results are used as a reference to prove the type of protein interaction. The formulated model is directed to coherently explain the flux changes of each protein involved in the system and stimulate easily. The simulation provides an overview of the protein dynamics in the system over time. Finally, the mathematical models and simulations will complement the basic understanding of the effect of glucose absorption on the translocation of GLUT4.